2010
DOI: 10.1007/s00227-010-1396-6
|View full text |Cite
|
Sign up to set email alerts
|

Stressed, but not defenceless: no obvious influence of irradiation levels on antifeeding and antifouling defences of tropical macroalgae

Abstract: The production of defence metabolites is assumed to be costly in metabolic terms. If this holds true, low-light stress should reduce the ability of seaweeds to defend themselves chemically against herbivory and fouling. We investigated the eVect of energy limitation on the defensive status of seaweeds by assessing their attractiveness to mesograzers and their activity against a bivalve macrofouler in comparison with non-stressed conspeciWcs. The macroalgae Codium decorticatum (Woodw.) M. Howe, Osmundaria obtus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
5
0
2
Order By: Relevance
“…While numerous studies demonstrated defense induction against herbivores in marine macroalgae in recent years (reviewed in Toth & Pavia 2007), so far none have rigorously demonstrate incurring costs (e.g. Pansch et al 2009, Appelhans et al 2010; but see Dworjanyn et al 2006 for costs of constitutive defense against fouling).…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies demonstrated defense induction against herbivores in marine macroalgae in recent years (reviewed in Toth & Pavia 2007), so far none have rigorously demonstrate incurring costs (e.g. Pansch et al 2009, Appelhans et al 2010; but see Dworjanyn et al 2006 for costs of constitutive defense against fouling).…”
Section: Introductionmentioning
confidence: 99%
“…Pansch, Cerda [35] found no effect of light limitation on chemically mediated defences against grazers and foulers in four brown algae from the coast of Chile and Appelhans, Lenz [34] reported the same for five seaweed species from the coast of Brazil (one green, two red, two brown including S. zonale). In contrast to this, Kubicek, Bessho [64] observed that grazing rates of the snail Lacuna smithii on the red alga Chondrus yendoi increased with decreasing light availability.…”
Section: Consequences Of Light Limitation For Algal Growth and Grazermentioning
confidence: 88%
“…Macroalgas marinhas alvos de estudos de ecologia química marinha no Brasil. Soares et al 2003Pereira et al 2004Weidner et al 2004Appelhans et al 2010 As macroalgas pardas (Phaeophyceae) comumente produzem terpenóides, polifenóis, substâncias de origem biossintética mista, terpenoaromático, e hidrocarbonetos voláteis como seus metabólitos secundários mais comuns (Blunt et al 2011 e revisões prévias deste autor). Um estudo pioneiro da Ecologia Química Marinha brasileira foi realizado com a macroalga parda Sargassum furcatum, e compreendeu a avaliação da atuação de polifenóis como defesa química contra a herbivoria (Pereira 1989).…”
Section: Macroalgas Marinhasunclassified
“…Dentre fatores ambientais, a irradiância, embora cause alterações nas taxas de fotossíntese e crescimento das macroalgas Codium decorticatum, Osmundaria obtusiloba, Pterocladiella capillacea, Sargassum vulgare e Stypopodium zonale, não afeta a produção de defesa química (Appelhans et al 2010). No entanto, fatores ambientais extremos caracterizando qualquer estresse são capazes de tornar macroalgas suscetíveis ao consumo por redução de suas defesas químicas (ex.…”
Section: 6unclassified